THE mCP STAR HD 9996 - PRECESSION OR NOT? - Bychkov, V. D.; Bychkova, L. V.; Madej, J.; Schatilov, A. V. (Одеські астрономічні публікації, 2010)
The star HD9996 have a long-period magnetic field of variations. On long-term variability was impose shorter variations conterminous with the orbital period.